PENGEMBANGAN SUMBER DAYA APARATUR PADA DINAS PERPUSTAKAAN DAN KEARSIPAN KOTA PROBOLINGGO - Astutik, Astutik; Indrawati, Mei; Winarto, Bambang (Program Pascasarjana Universitas Wijaya Putra Surabaya, 2024)
Purpose in this research is to know and analyze form knowledge development apparatus at the Library and Archives Office of the City of Probolinggo. The research method used is descriptive research approach qualitative, the data collection instruments are observational studies, documentation and interviews, while the data analysis used qualitative analysis. The results showed that the development of apparatus resources at the Library and Archives Service of the City of Probolinggo has been going quite well, including the development of apparatus knowledge, the development of employee capabilities/skills, the development of attitude And employee behavior. What needs to be improved is the development of self-competence through training for employees who have not yet improved their formal education, further improving education and training for employees.